Determinants of Profitability : Evidence from Construction Companies Listed on Indonesian Securities Market - Damar Jati; Heri Setiawan; Sodik Dwi Purnomo; Siti Muntahanah; Fatwa Zuhaena; Arinastuti Arinastuti (Universitas Ahmad Dahlan, Yogyakarta, 2023)
An asset management role is required to analyze and optimize revenue sources and efficient systems to reduce costs. Construction service companies that tend to have fewer fixed assets than their current assets have constraints in suppressing production prices and must be able to manage them efficiently to maintain their existence in the market. The data shows the growth in the number of construction service companies which continues to increase and the construction price index which continues to decline, requiring efficient asset management to reduce production costs. For this reason, this study aims to determine the effect of Account Receivable Turnover (ARTO) asset management instruments, Fixed Asset Turnover (FATO), Inventory Turnover (IT), and Total Asset Turnover (TATO) on Operating Profit Margin (OPM) in construction service companies in Indonesia. The research sample is 5 large-scale construction companies in Indonesia with vulnerable observation periods from 2017 to 2021. The method used in this research is panel data regression to examine the relationship between research variables. The results of this study indicate that Fixed Asset Turnover (FATO) and Total Assets Turnover (TATO) have an effect on the Operational Profit Margin (OPM) of construction service companies in Indonesia. Meanwhile, Account Receivable Turnover (ARTO) and Inventory Turnover (IT) have no effect on OPM in Indonesian construction service companies. The results of this study have implications for construction service companies that asset management is very important for the company's progress, especially in increasing profits. This research contributes to the ability of construction service companies to manage their assets effectively, because the construction service business actor is the party responsible for implementing infrastructure development in Indonesia.